Validity of the Kihon Checklist for assessing frailty status. Issue 6 (14th July 2015) - Satake, Shosuke; Senda, Kazuyoshi; Hong, Young‐Jae; Miura, Hisayuki; Endo, Hidetoshi; Sakurai, Takashi; Kondo, Izumi; Toba, Kenji
Abstract : Aim: The Kihon Checklist is extensively used in Japan to identify elderly persons who are at risk of requiring support/care. We aimed to determine whether or not the Kihon Checklist can estimate frailty status defined by the Cardiovascular Health Study criteria. Methods: This cross‐sectional study evaluated the Kihon Checklist and activities of daily living based on self‐records maintained with the assistance of nurses in a convenience sample of 164 elderly outpatients who lived without care or support. Body composition was measured using dual energy X‐ray absorptiometry. Physical functions, nutritional status, cognitive function and depressive mood were assessed using standardized evaluations. Frailty status was evaluated using the Cardiovascular Health Study frailty criteria. Results: The total Kihon Checklist score closely correlated with validated assessments of physical functions, nutritional state, cognitive function, depressive mood and the number of frailty phenotypes defined by the Cardiovascular Health Study criteria (ρ = 0.655, P < 0.001). The area under the receiver operating characteristics curves for the evaluation of frailty status was 0.81 for prefrailty and 0.92 for frailty. The sensitivity and the specificity were 70.3% and 78.3% for prefrailty, and 89.5% and 80.7% for frailty at total Kihon Checklist scores of 3/4 and 7/8, respectively. Conclusion: The Kihon Checklist is a useful tool for frailty screening. Analyzing the results of this self‐reporting questionnaire, together with other more high‐tech screening modalities, will cost‐effectively improve the quality of life for many elderly individuals in a timely manner.Geriatr Gerontol Int 2015; ●●: ●●–●●.